Study of Customer Loyalty Through Brand Trust and Service Quality with Intervening Variables of Customer Satisfaction at Meatlovers - Pratiwi, Mona Inayah; Utami, Hadiahti -; Kurniani, Kurniani -; Saleh, Khairul -; Prasetya, Budi - (Politeknik Negeri Semarang, 2025)
Loyalty refers more to the behavioral form of decision-making units to make continuous purchases of the products of a selected company.The purpose of this study was to determine Customer Loyalty through Brand Trust and Service Quality with the Intervening Variable Customer Satisfaction at Meatlovers Outlets in Semarang City. by measuring indicators that affect the variables of Customer Loyalty, Brand Trust, Service Quality and Customer Satisfaction. The population of this study were consumers of Meatlovers outlets in Semarang City. While the sampling technique used in this research is the Purposive Sampling Method. The number of research samples is 100-200 samples from the total population of respondents. This research technique uses two approaches: 1). Confirmatory factor analysis, in Structural Equation Modeling (SEM); and 2). Regression Weight on Structural Equation Modeling (SEM). The model output in this study can make a positive contribution to Meatlovers outlets in Semarang City in an effort to be able to realize the continuity and sustainability of their business in customer satisfaction, both in the form of managerial implication suggestions and the formulation of scientific articles and measurement instruments. Managerial advice is aimed at Meatlovers outlets in formulating strategies to maintain their business so that consumers come back to buy Meatlovers outlet products.